Liderança na profissão contábil: a trajetória profissional das presidentas de conselhos regionais de contabilidade - Oliveira, Marcela Ferreira (2020)
The inclusion of women in the labor market came in a scenario full of inequalities and discrimination. Then, the Waves of Feminism arised to try to gradually subtract the gender distinction and to pursue an egalitarian society that respects the personal identity in addition to gender stereotyping. However, decades later, feminist struggles have not yet fully reached their goal and women continue to suffer social discrimination, especially when they decide to subvert sexist narratives of power and occupy places considered as masculine, such as the presidency of an entity. With a qualitative and exploratory nature, supported by Gender Theories and the “glass ceiling” phenomenon (invisible barriers that hinder professional growth), this study aimed to investigate, in the trajectory of women who hold the presidency in the Regional Accounting Councils (CRC), what are the motivating and motivating elements, as well as the barriers and difficulties for them to occupy the presidencyTo achieve the objective, semi-structured interviews were conducted with the seven elected chairwomen, who presided during the 2018-2019 term. These interviews were analyzed using Content Analysis and the Critical Incident Technique with the aid of the QSR-Nvivo software. The main finding of the research is that the barriers and difficulties were mitigated through the gender stereotypes conceived by the chairwomen, who saw these factors as boosters in their trajectories. This is due to the fact that discrimination is beyond the Councils and literature, is intrinsic in the structure of society, between the lines of relationships - which naturalizes and, at times, makes the symbolic violence suffered imperceptible, but does not prevent the breaking of barriers and the breaking of the 'glass ceiling', with regard to the rise to leadership positions as investigated in this research. Based on the narratives, the importance of personal and professional influences, such as family and Council support, mainly the sorority of other women, was confirmed to demystify the stereotypes of female incapacity intrinsic in the Councils structure. It was also found that the professional appreciation perceived by all chairwomwn results in a feeling of professional fulfillment and social representativeness, with respect to the importance they attach to the position occupied by them as leadership. The speeches also pointed out that gender and generalization were present throughout the professional career of the CRC chairwomen, even though such gender distinction was not noticed or considered as a factor of difficulty by them due to the positioning strategies to maintain their career and their professional position.